Pemikiran Pendidikan Islam Syekh Nawawi Al-Bantani: Paradigma Pengajaran Multidimensi - Muhammad, Hasman Zhafiri; Imawan, Dzulkifli Hadi; Majid, Muhammad Fuad Fathul (Lembaga Sosial Rumah Indonesia, 2023)
This research aims to analyze the educational thought of Syekh Nawawi Al-Bantani. Influenced significantly by his father and prominent scholars, Syekh Nawawi's profound love for religious knowledge motivated him to pursue various disciplines, emphasizing the obligation of seeking knowledge for the intellectually inclined. The study employs a literature review method to analyze the role of Syekh Nawawi Al-Bantani in Islamic education in Nusantara. Data were obtained from primary and secondary literature sources, including scholarly articles and books. Descriptive analysis with triangulation techniques was used to verify and complement the data. The findings highlight Syekh Nawawi Al-Bantani's perspective on education, emphasizing the importance of understanding the universe's existence, human potential, and the purpose of education, while promoting holistic development encompassing physical, intellectual, and spiritual aspects. The implications of his teachings are valuable for contemporary educators, guiding the integration of Islamic values in education and fostering gratitude, humility, and a commitment to lifelong learning, thus producing morally upright individuals actively contributing to society.